Antibody–Drug Conjugates in Cancer Therapy - Xiaoling Lu; Yujie Wang; Xin Cao; Yuping Zhu (Highlights on Medicine and Medical Research Vol. 1, 2021)
Antibody–drug conjugates (ADCs), constructed with monoclonal antibodies, linkers, and natural cytotoxins, are innovative drugs developed for oncotherapy. Owing to the distinctive advantages of both chemotherapy drugs and antibody drugs, ADCs have got enormous success during the past several years. The development of highly specific antibodies, novel marine toxins’ applications, and innovative linker technologies all accelerate the rapid R&D of ADCs. Meanwhile, some challenges remain to be solved for future ADCs. For instance, varieties of site-specific conjugation have been proposed for solving the inhomogeneity of DARs (Drug Antibody Ratios). In this review, the usages of various natural toxins, especially marine cytotoxins, and the development strategies for ADCs in the past decade are summarized. Representative ADCs with marine cytotoxins in the pipeline are introduced and characterized with their new features, while perspective comments for future ADCs are proposed. Site-specific conjugation technology has caught numerous pharmaceuticals companies’ eyes for solving the inhomogeneity problem to some extent, pointing out the way to further development of ADCs. With the advancement of conjugation technology, a variety of conjugated groups have been designed and connect with many different drugs by the diversified modification of linkers.